The Low Cost Green Car (LCGC) Program in Islamic Perspective - M. Muhfiatun; Susi Riyantika (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2016)
Recently the Government of Indonesia makes a program of Low Cost Green Car (LCGC). The purpose of the program is to support the independence LCGC four-wheeled vehicles industry in order to anticipate the trend of increased demand for energy-efficient motor vehicles and reasonably priced. LCGC program is polemical prolonged. Protests came from all circles. Such as Local Officials, to the Economist. Because the program is properly designed like a cheap car city so that it’s bought by urban communities only According to The Ministry of Industry Article 1 (e) that the Green Car is set up with the price of Rp. 95,000,000.00 (ninety five million). In this case, the government intervened by way Ceiling Price although this intervention thresholds given in the event of structural changes in Indonesia's economic fundamentals, but the policy of intervention was assessed inconsistently. Because the car LCGC-called